IL-4 Inhibits IL-1β-Induced Depressive-Like Behavior and Central Neurotransmitter Alterations - Hyun-Jung Park; Hyun-Soo Shim; Kyungeh An; Angela Starkweather; Kyung Soo Kim; Insop Shim (Hindawi Limited, 2015)
It has been known that activation of the central innate immune system or exposure to stress can disrupt balance of anti-/proinflammatory cytokines. The aim of the present study was to investigate the role of pro- and anti-inflammatory cytokines in the modulation of depressive-like behaviors, the hormonal and neurotransmitter systems in rats. We investigated whether centrally administered IL-1β is associated with activation of CNS inflammatory pathways and behavioral changes and whether treatment with IL-4 could modulate IL-1β-induced depressive-like behaviors and central neurotransmitter systems. Infusion of IL-4 significantly decreased IL-1β-induced anhedonic responses and increased social exploration and total activity. Treatment with IL-4 markedly blocked IL-1β-induced increase in PGE2 and CORT levels. Also, IL-4 reduced IL-1β-induced 5-HT levels by inhibiting tryptophan hydroxylase (TPH) mRNA and activating serotonin transporter (SERT) in the hippocampus, and levels of NE were increased by activating tyrosine hydroxylase (TH) mRNA expression. These results demonstrate that IL-4 may locally contribute to the regulation of noradrenergic and serotonergic neurotransmission and may inhibit IL-1β-induced behavioral and immunological changes. The present results suggest that IL-4 modulates IL-1β-induced depressive behavior by inhibiting IL-1β-induced central glial activation and neurotransmitter alterations. IL-4 reduced central and systemic mediatory inflammatory activation, as well as reversing the IL-1β-induced alterations in neurotransmitter levels. The present findings contribute a biochemical pathway regulated by IL-4 that may have therapeutic utility for treatment of IL-1β-induced depressive behavior and neuroinflammation which warrants further study.